IMPLEMENTASI PEMBELAJARAN TEMATIK BERBASIS GERAKAN LITERASI SEKOLAH SEKOLAH DASAR NEGERI 28 PONTIANAK UTARA - Siasusiati Siasusiati; Asrori Asrori; Sulistyarini Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to describe the implementation of thematic learning based on the literacy movement of 28 Pontianak Utara Elementary School. This research is a descriptive study with a qualitative approach. The subjects of this study were the principals, teachers, and class V and VI students of SD Negeri 28 Pontianak Utara. Data collection is done by conducting observations, interviews, and documentation. The results showed that the implementation of thematic learning based on the school literacy movement was as follows: (1) the planning that the teacher in making the planning of the implementation of thematic learning had included the activities of the school literacy movement. (2) in its implementation that teachers and students have implemented literacy activities in teaching and learning activities. (3) there are supporting and inhibiting factors in the implementation of thematic learning based on the school literacy movement, namely the limited available book resources.Keywords: Implementation of Thematic Learning, School Literacy Movement.